Pendapatan Usaha Pupuk Organik Bio Fertilizer Produksi Mont Ayahanda Di Desa Lambro Bileu Kecamatan Kuta Baro Kabupaten Aceh Besar - Said Ahmad Sabri; Amrusi Amrusi; Zakaria Zakaria (Universitas Syiah Kuala, 2019)
The research, entitled Revenues Organic Fertilizer Exertion Bio Fertilizer Ayahanda Mont Production in Lambro Bileu village of Kuta Baro Sub-district, Aceh Besar District has several problem formulation which are how much revenue obtained from organic fertilizer bio fertilizer Ayahanda Mont Production in Lambro Bileu Village, Kuta Baro Sub-district, Aceh Besar District and how the distribution channel system employed in the marketing of organic fertilizer bio fertilizer Ayahanda Mont Production in Lambro Bileu Village, Kuta Baro Sub-district, Aceh Besar District.The purpose of this research is to know the amount of revenue obtained from organic fertilizer bio fertilizer Ayahanda Mont Production in Lambro Bileu Village, Kuta Baro Sub-district, Aceh Besar District.This research employes quantitative approach with descriptive research type. The object of this research is the revenue of bio fertilizer organic fertilizer with the research subject that is the owner and the employee of organic fertilizer bio fertilizer Ayahanda Mont Production in Lambro Bileu Village, Kuta Baro Sub-district, Aceh Besar District which is done for 1 year and divided into two periods, they are July until December 2015 and January to June 2016. Data collection techniques employed are interviews, observation and documentation. To analyze the net revenue of the exertion then the analysis employed is the production of fixed costs, the production of variable costs, the production of total cost and revenue.So, from the results of the data analysis found net revenue or profits derived from the production of organic fertilizer bio fertilizer Ayahanda Mont Production in the period July-December 2015 amounted to Rp74.024.925, - and in the period January-June 2016 amounted to Rp76.257.625, -.From the profit gained in the two periods, we can conclude that the production of organic fertilizer bio fertilizer Ayahanda Mont Production is increasingly growing as seen from the increase of profit in each period, where the net revenue obtained in the period of January-June 2016 is greater than net income at Previous period (July-December 2015 period).